AWOL: Canada's defence policy and presence in the Asia Pacific. (March 2018) - Dewitt, David; Young, Mary; Brouse, Alex; Piereder, Jinelle
Our focus is on Canadian defence and security activities in the Asia Pacific arena between 1990 and 2015. While governments have asserted the growing primacy of the Asia Pacific, we ask the following: What does Canada's recent military and security record tell us about the policies and operational aspects of Canadian engagement? How might we assess these in comparison with Ottawa's declared importance of the Asia Pacific? What might this tell us about the near-term future of Canada's role and pursuit of interests and opportunities in this complex region? We present and analyze empirical materials drawn from primary sources that inform an assessment of Canada's presence in the defence and security agenda of the Asia Pacific, during the period that saw Canadian governments declare a deep interest in relations with the Asia Pacific, yet fail to make Canada a full partner with sustained commitments.